Effect of Consuming Papaya Leaves, Almond Milk, Green Beans, Moringa Leaves, Ajwa Dates, Soy Milk, and Fennel Leaves on Breast Milk Production in Postpartum Mothers - Ita Herawati; Lita Lutfiah; Nur’aini Djulkiyyah Rahmawati; Christine Natalia; Firnia Santi; Dede Maemunah; Ise Susanti; Rita Kurni (Postgraduate, University of Mataram, 2024)
Exclusive breastfeeding rates are often low due to suboptimal breast milk production, which impedes infants' nutritional needs. This issue is frequently attributed to poor maternal nutrition, unbalanced diets, and irregular food consumption. Breast milk production relies on hormonal changes, notably the dominance of prolactin over progesterone and estrogen during childbirth. To address this, a study was conducted to evaluate the impact of specific foods boiled papaya leaves, almond milk, green beans, moringa leaves, ajwa dates, soy milk, and fennel leaves—on breast milk production. Employing a quasi-experimental design with a one-group pretest-posttest approach, the study involved 56 postpartum mothers whose milk production was substandard. These participants were selected in March 2023 using purposive non-probability sampling. A paired t-test was performed for bivariate analysis. Results indicated a significant improvement in milk production, with a p-value of 0.000, demonstrating that the consumption of these foods positively affects lactation. Consequently, it is recommended that breastfeeding mothers incorporate these foods into their diet to enhance milk production and support exclusive breastfeeding. Regular consumption of these specific foods can help meet infants' nutritional needs more effectively.